Maximizing participant retention in a phase 2B HIV prevention trial in Kampala, Uganda: The MTN-003 (VOICE) Study. Issue 5 (3rd September 2018) - Wynne, Joshua; Muwawu, Rosemary; Mubiru, Michael C; Kamira, Betty; Kemigisha, Doreen; Nakyanzi, Teopista; Kabwigu, Samuel; Nakabiito, Clemensia; Kiweewa Matovu, Flavia
Abstract : Background: The success of longitudinal trials depends greatly on using effective strategies to retain participants and ensure internal validity, maintain sufficient statistical power, and provide for the generalizability of study results. Objective: This paper describes the challenges and specific strategies used to retain participants in a Phase 2B safety and effectiveness study of daily oral and vaginal tenofovir formulations for the prevention of HIV-1 infection in the MTN-003 (VOICE) trial in Kampala, Uganda. Methods: Once enrolled, participants were seen every 28 days at the research site and their study product was re-filled. Challenges to retention included a mobile population, non-disclosure of study participation to spouse/family, and economic constraints. Strategies used to maintain high participation rates included the use of detailed locator information, a participant tracking database, regular HIV/STI testing, and the formation of close bonds between staff and subjects. Results: We enrolled 322 women out of the 637 screened. The overall retention rate was 95% over a 3 year follow up period. Only 179 (3%) out of the 6124 expected visits were missed throughout study implementation. Reasons for missed visits included: participants thinking that they did not need frequent visits due to their HIV negative status, time constraints due to commercial sex work, and migration for better employment. Conclusions: With the implementation of multi-faceted comprehensive follow-up and retention strategies, we achieved very high retention rates in the MTN-003 study. This paper provides a blueprint for effective participant retention strategies for other longitudinal HIV prevention studies in resource-limited settings in Sub-Saharan Africa.